Kinetic Continuous Opinion Dynamics Model on Two Types of Archimedean Lattices - Lima, Francisco W. S. (Frontiers in Physics, 2017)
Here, the critical properties of kinetic continuous opinion dynamics model are studied on ($4,6,12$) and ($4,8^2$) Archimedean lattices. We obtain $p_c$ and the critical exponents from Monte Carlo simulations and finite size scaling. We found out the values of the critical points and Binder cumulant that are $p_c=0.086(3)$ and $O_4^*=0.59(2)$ for ($4,6,12$); and $p_c=0.109(3)$ and $O_4^*=0.606(5)$ for ($4,8^2$) lattices and also the exponent ratios $\beta/\nu$, $\gamma/\nu$ and $1/\nu$ are respectively: $0.23(7)$, $1.43(5)$ and $ 0.60(3)$ for ($4,6,12$); and $0.149(4)$, $1.56(4)$ and $0.94(4)$ for ($4,8^2$) lattices.